2017
DOI: 10.1002/rrq.178
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Structured Teacher Adaptations to an Evidence‐Based Summer Literacy Program

Abstract: The authors conducted a cluster‐randomized trial to examine the effectiveness of structured teacher adaptations to the implementation of an evidence‐based summer literacy program that provided students with (a) books matched to their reading level and interests and (b) teacher scaffolding for summer reading in the form of end‐of‐year comprehension lessons and materials sent to students’ homes in the summer months. In this study, 27 high‐poverty elementary schools (75–100% eligibility for free or reduced‐price … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
38
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(45 citation statements)
references
References 67 publications
7
38
0
Order By: Relevance
“…We agree with this outlook wholeheartedly and commend the schools of education who have answered the call in preparing teachers to deliver multileveled reading instruction (e.g., Ivey & Johnston, ; Kim, Burkhauser, et al., ; Kim, Hemphill, et al., ). For although it is obvious that learning to read is necessary for optimal development, there is a complementary view that learning to read in and of itself is not sufficient (Stanovich & Cunningham, ).…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…We agree with this outlook wholeheartedly and commend the schools of education who have answered the call in preparing teachers to deliver multileveled reading instruction (e.g., Ivey & Johnston, ; Kim, Burkhauser, et al., ; Kim, Hemphill, et al., ). For although it is obvious that learning to read is necessary for optimal development, there is a complementary view that learning to read in and of itself is not sufficient (Stanovich & Cunningham, ).…”
Section: Discussionsupporting
confidence: 62%
“…These suggestions align with elementary students’ reports of enjoying choice, receiving guidance, and hearing the views of teachers and peers (Edmunds & Bauserman, ). Kim and colleagues (Kim, Burkhauser, et al., ; Kim, Hemphill, et al., ) also emphasized that interesting and accessible books are critical to student engagement. The data presented here suggest that in addition to knowing the interests and reading levels of students, teachers with more personal reading experience and more knowledge about print exposure may be advantaged when promoting reading activities in their classrooms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Encouraging parents to engage in many home literacy activities with their children in the upper grades of primary school might therefore have positive effects on the reading interest and reading skills of this age group. For example, a recent study of a summer literacy program targeting fourth graders showed that children's reading comprehension increased when parents monitored their children's comprehension of books that were matched on children's interests and reading level (Kim et al, 2017). Future studies might examine the relations between children's reading interest and skills and the ways through which these can be impacted through their parents' involvement in more detail and longitudinally.…”
Section: Parents Adjust Their Home Literacy Environmentmentioning
confidence: 99%
“…National reading campaigns should make parents aware of the importance and benefits of engaging in home literacy activities, such as sharing their own books and discussing books or articles (Kim et al, 2017;Klauda, 2009), even when children are able to read independently. These activities should take place in a positive affective atmosphere as it has been shown that children whose parents consider reading a pleasurable activity have a more positive reading attitude than children whose parents focus on skills instruction (Baker, Scher, & Mackler, 1997;Britto & Brooks-Gunn, 2001;Sonnenschein & Munsterman, 2002).…”
Section: Implications For Practice Application Theory and Policymentioning
confidence: 99%